Separation of Molar Weight-Distributed Polyethylene Glycols by Reversed-Phase Chromatography—II. Preparative Isolation of Pure Single Homologs - Supper, Malvina; Jost, Rosanna; Bornschein, Benedikt; Kaspereit, Malte (Processes, 2023)
The isolation of single homologs of polyethylene glycol by preparative reversed-phase chromatography is investigated. A thermodynamic model developed accurately previously describes the retention times of individual homologs as function of their size, temperature, and mobile phase composition under linear, diluted conditions. The model is extended to predict limiting retention times for linear gradient operation in preparative applications. Isocratic and gradient-based separations are studied under strongly overloaded conditions. Baseline separation of homologs up to 3000 g/mol is demonstrated. Quantitative production of pure single homologs up to molar weights of 1000 g/mol was performed using an automated setup.<br